Analysis of Energy Structure in Northeast China. Issue 4 (March 2021) - Lin, Mingwei
Abstract: As the old industrial base of our country, the utilization of energy in Northeast China has a certain influence on the implementation of the overall strategy of our country. After comparing and analyzing the data, it is concluded that the primary energy sources such as coal and oil account for a large proportion in the energy production and consumption structure of Northeast China, and after SPSS time series forecast, it is known that the energy structure will not change much in the short term. In view of this problem, we can promote the improvement and development of energy structure in Northeast China by developing new energy economy, perfecting the system of laws and regulations related to energy, and developing or introducing energy saving and efficiency-enhancing technology to improve energy utilization efficiency.Energy is the material basis for the survival and development of human society, and the revolution and innovation of energy is also an important manifestation of a country's comprehensive strength. As the old industrial base of our country, Northeast China has abundant energy reserves such as coal and oil, and its energy utilization has a certain influence on the implementation of the overall strategy of our country. In October 2003, the CPC Central Committee and the State Council issued "Some Opinions on the Implementation of the Revitalization Strategy of the Old Industrial Base in Northeast China", which clarified the guiding ideology, principles, tasks and policy measures for the implementation of the revitalization strategy. How to optimize the energy structure and make rational use of the energy in Northeast China will be an important issue to be considered in the energy innovation revolution in Northeast China. This paper will analyze the energy structure of Northeast China by means of data analysis, and then find out the problems and solutions [1] .